A critical analysis of the grammar of isiXhosa as used in the Revised Union version of the Bible - Oosthuysen, Jacobus Christiaan (Rhodes University, Faculty of Humanities, School of Languages, 2013)
This study provides a description and critical analysis of the grammatical structure of isiXhosa as used in the Revised Union Version of the Bible, published in 1942 and republished in 1975. This translation records what was regarded as proper isiXhosa at the beginning of the 20th century, reflecting the consensus inter alia of prominent isiXhosa writers, such as W.B. Rubusana, J.H. Soga, C. Koti, Y. Mbali and D. D. T. Jabavu, who served on the committee that produced the revision. In this study isiXhosa is described in its own right, without approaching it with preconceived ideas derived from other languages. That is to say this is a phenomenological analysis describing the grammatical structures of isiXhosa as they present themselves to the analyst. It is comprehensive, with no structure being overlooked or being described in such a manner that it complicates an understanding of other structures. In the first chapter the context of the research and a brief outline of the historical growth in understanding the structure of isiXhosa are set out and the goals and the method followed in this study are described. In the following chapters the findings of this study are presented. The initial focus is on isiXhosa phonology and the orthography used to put it to writing. Then isiXhosa morphology and syntax is set out. Initially the substantives, i.e. the nouns and pronouns in their distinctive classes and forms, and how they are qualified, receive attention. Then the predicates are explored, i.e. the verbs and copulatives, as linked to the substantives with concords, and reflecting various moods, tenses, actualities and aspects. Finally attention is given to ideophones and interjections and words that can be grouped together as adverbs, conjunctions, avoidance words and numerals. In the concluding chapter consideration is given to the question of whether this study has in fact achieved the aim of setting out a description of the structure of isiXhosa based solely on the language itself, free of preconceived ideas, and attention is drawn to insights gained in respect of the true nature of the isiXhosa grammatical structures, such as, for example, the variable prefix qualificative nouns, traditionally referred to as adjectives. This study is therefore a revisionist study in the sense that it reinvents isiXhosa as a language in its own right, free from Western influenced perspectives.
Keywords: Bible -- Xhosa -- Revised Union -- 1942; Xhosa language -- Grammar -- Research; Xhosa language -- Texts